Strategi Program Work Life Balance Dan Pola Asuh Otoritatif Dalam Mendidik Anak - Rizky Gunawan; Aditya Vernando (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to find out the parents' strategies in educating and developing children from early childhood to adulthood and the role of parents in balancing work and family or work life balance in daily life. The results of this study indicate that parents have several obstacles and factors in implementing the concept of work life balance, but have one strategy, namely authoritative parenting. Patterns that are combined between Authoritarian Parenting and Pessimistic Parenting. This can be seen from the 2 dimensions given, namely the Control and Warmth Dimensions, this process must also be carried out consistently and responsibly so that it is well implemented. The research uses qualitative methods with descriptive research types. With secondary data sources through national and international journal articles and using other sources such as online media, social media (youtube, instagram, facebook, and twitter). From the results mentioned, it can be concluded that work and personal life as well as the role of parents in educating children are the most important things in order to create a golden generation, where generations are able to provide polite attitudes, carry out responsibilities for work and personal life, and the most important thing is that children are able to become people who carry out all their activities in the social environment properly